2015
DOI: 10.1016/j.neuropsychologia.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Differential contributions of hippocampus and medial prefrontal cortex to self-projection and self-referential processing

Abstract: Converging evidence points to a neural network that supports a range of abilities including remembering the past, thinking about the future, and introspecting about oneself and others. Neuroimaging studies find hippocampal activation during event construction tasks, and patients with hippocampal amnesia are impaired in their ability to (re)construct events of the past and the future. Neuroimaging studies of constructed experiences similarly implicate the medial prefrontal cortex (mPFC), but it remains unknown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
156
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 145 publications
(169 citation statements)
references
References 110 publications
10
156
0
Order By: Relevance
“…We restricted analyses to these 90 s descriptions of a specific moment of the (re)constructed event. In the original analysis of these data, Kurczek et al (2015) found that the patients with hippocampal amnesia produced narratives that contained significantly fewer episodic details, across all time periods, consistent with the literature (Race et al, 2011). Sessions were video- and audio-taped for analysis.…”
Section: Methodssupporting
confidence: 66%
See 3 more Smart Citations
“…We restricted analyses to these 90 s descriptions of a specific moment of the (re)constructed event. In the original analysis of these data, Kurczek et al (2015) found that the patients with hippocampal amnesia produced narratives that contained significantly fewer episodic details, across all time periods, consistent with the literature (Race et al, 2011). Sessions were video- and audio-taped for analysis.…”
Section: Methodssupporting
confidence: 66%
“…The current study is a reanalysis of data reported by Kurczek et al (2015). In that study, participants were given a neutral cue word (bird, clock, farm, garden, hotel, lake, radio, restaurant, river, snow, teacher, truck) and asked to produce 12 narratives, including three unique narratives of autobiographical events occurring in each of four time periods (Real Past, Imagined Past, Imagined Present, and Future).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, some evidence indicates that these may not be mutually exclusive hypotheses, and that varying functional roles may be differentially undertaken by distinct components of the same circuitry. For instance, Kurczek et al (2015) reported that compared to healthy matched control participants, neurological patients with lesions of the medial prefrontal cortex showed impairments in self-referential evaluation but not selfprojection, whereas patients with lesions of the medial temporal lobe showed the opposite pattern in that they were impaired in self-projection but not self-referential thinking (Kurczek et al, 2015).…”
Section: Intentionality-based Imagination (Recollective/social)mentioning
confidence: 99%